An analysis of foreign residents' perceptions and behaviors regarding digital government portal services in the Republic of South Korea. (June 2023) - Aftab, Muhammad; Myeong, Seunghwan
Governments have made significant investments to deliver information and services to governmental institutions, citizens, and businesses through e-services. The re-adoption of such governmental services has been focused on in various studies. However, this study focuses on the post-adoption of digital government services and information system quality. Therefore, evaluating the digital government portal services from the user's perspective is important. This study proposes an expanded conceptual framework that includes confirmation of expectation and perceived functional benefits as mediating variables based on continuance literature and information systems' performance. Online and offline surveys were conducted to get the responses of emigrants in the Republic of Korea to assess the proposed relationship among the variables. Overall, 371 samples were collected and analyzed. The regression and mediation analyses were performed using the Macro PROCESS model. The results indicate that confirmation of expectation and perceived functional benefits significantly predict the foreigners' continuance intention as Korean digital government websites users. The study also confirms the direct and indirect impacts of digital government services quality factors on continuance intention through perceived functional benefits. However, it does not find evidence for the influence of confirmation of expectation as a mediator. The research concludes with positive implications for academicians, governmental policymakers, and the overall body of knowledge. Points for practitioners: The results of this study indicate that government officials should concentrate on technical features and psychological characteristics to understand people's intention for e-service continuance. The relation of digital government facilities with perceived functional benefits enables lawmakers to establish responsive and quick service portal systems. Besides, the government can help users by providing 24-hour customer support, electronic assistance desks, and users' manuals to increase the consistent use and efficiency of government systems.